The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3906/zoo-1411-25
|View full text |Cite
|
Sign up to set email alerts
|

New locality record of Podarcis tauricus tauricus (Pallas, 1814) (Squamata: Lacertidae) from the western Black Sea region of Turkey

Abstract: distinguished from P. t. tauricus by the following: large SVL; more pointed head; the tail length is nearly twice the length of the head and body; thickness of neck not constricted; frontal shield as long as frontoparietal; occipital shield as long as or a little longer than the interparietal shield; feebly keeled dorsum scales; less-pointed caudal scales (Lehrs, 1902). P. t. thasopulae is different from P. t. tauricus in having a more yellowish and mustard-colored ventral region, and a brownish and bronze-col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Field observations carried out in Türkiye in recent years have revealed that some amphibian and reptile species exist in the country (Bülbül et al, 2016). In addition, these studies have shown that some species known to exist in Türkiye are also found in different geographical regions where they were not previously distributed (Bülbül et al, 2015;Olgun et al, 2015;Candan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Field observations carried out in Türkiye in recent years have revealed that some amphibian and reptile species exist in the country (Bülbül et al, 2016). In addition, these studies have shown that some species known to exist in Türkiye are also found in different geographical regions where they were not previously distributed (Bülbül et al, 2015;Olgun et al, 2015;Candan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…1) between the years 1977 and 2019 (mostly after 1990) and 10% of the occurrence records have coordinates. The species occurrence records that were used to construct the articles were as follows: Altunışık et al, 2016;Başoğlu & Baran, 1977;Bülbül et al, 2015;Cogălniceanu et al, 2013;Çördük et al, 2018;Eroğlu et al, 2017;Fischer et al, 2019;Iftime & Iftime, 2016;Koç et al, 2018;Kukushkin & Doronin, 2013;Mollov & Valkanova, 2009;Petrov et al, 2006;Poulakakis et al, 2005aPoulakakis et al, , 2005bPsonis et al, 2017;Sokolov, 2019;Stănescu et al, 2013;Tomovic et al, 2018;Tok & Çiçek, 2014;Urošević et al, 2015 The Maxent algorithm assumes that all occurrence records on the study area are equally likely to be sampled (Merow et al, 2013). To reduce the clustering of occurrence points, caused by the survey bias, they were filtered (Boria et al, 2014;Kadmon et al, 2004) by 10 km, 15 km, and 20 km distance thresholds via using 'spatial thinning' application on the Wallace platform v. 1.0.6 (Kass et al, 2018) and; as a result, 20 Km spatial thinning with 153 occurrence points was used to construct the model due to 10 Km (243 occurrence points) and 15 Km (193 occurrence points) spatial thinning were not able to remove clustering (Fig.…”
Section: Occurrence Datamentioning
confidence: 99%
“…3). This could be due to several reasons: 1) Known distribution area of the species is expanded with new studies (Tok & Çiçek, 2014;Bülbül et al, 2015;Gül & Tosunoğlu, 2017;Fischer et al, 2019) and the results of the study might support it, 2) Italy and the south part of Dinaric Alp Mountains are not inside the distribution area of the species historically, even though it had been, the barrier status of the Alps could have blocked northwards directed range expansions from the Italian Peninsula (Sudhaus et al, 1997). Likewise Italy, Sicily was also overpredicted and these findings could be the result of modelling weakness.…”
Section: The Present the Past And The Future Distribution Pattern Of ...mentioning
confidence: 99%
See 1 more Smart Citation